Differences in the Concentration and Composition of Human Milk Components Are Related to Variation in Milk and Infant Fecal Microbiomes. (29th May 2020) - Pace, Ryan; Williams, Janet; Lackey, Kimberly; McGuire, Mark; McGuire, Michelle; ,
Abstract: Objectives: Profiles of human milk oligosaccharides (HMO) and milk/infant fecal microbiota vary globally. However, associations between and among HMO, other milk-borne factors (e.g., lactose, protein), and milk/infant fecal microbiomes have not been well-investigated. Here we tested the hypothesis that variations in milk lactose, protein, and HMO concentrations are associated with variations in the structure of milk and infant fecal microbial communities. Methods: Milk/infant fecal samples from 357 maternal-infant dyads collected as part of the INSPIRE study from 11 geographically/culturally diverse sites located in eight countries (Ethiopia, The Gambia, Ghana, Kenya, Peru, Spain, Sweden, and USA) were analyzed. DNA was extracted and bacterial 16S rRNA V1V3 hypervariable region amplified/sequenced for microbiome analysis. HMO, lactose, and protein profiles were generated from HPLC and spectrophotometric assays. Results: Milk and infant feces share many of the same abundant bacterial genera, while also containing unique bacterial communities. Community states type (CST) analyses indicate both sample types group into a relatively small number of discrete communities characterized by enrichment of specific taxa (e.g., Streptococcus, Bifidobacterium ). Concentrations of milk lactose and protein varied by population/CST. Additionally, variation in the microbial community structure of milk and infant feces was associated with concentrations of total/individual HMO, lactose, and protein. Conclusions: Similar to HMO concentrations, milk lactose and protein vary globally. Variations in milk and infant fecal microbial communities are associated with those of milk lactose, protein, and HMO concentrations. Given these results, as well as prior data on the influence of other environmental variables (e.g., pumped vs. direct breastfeeding), additional longitudinal studies are needed to better understand this complex network of maternal-infant-microbe interactions with respect to environmental factors and how differences impact postnatal maternal-infant health. Funding Sources: National Science Foundation (award 1, 344, 288), National Institutes of Health (R01 HD092297), and USDA.